Post a New Question

math

posted by on .

i solved by factoring like this:
3x^2+5x-12=0
(3x+4)(x-3)
-4 +3
x=-4 x=3

now i need to solve by the form x^2=k
How do I do that?

  • math - ,

    3x^2 + 5x - 12 = 0
    This cannot be factored
    This can be solved by completing the square or using the quadratic formula.


    (3x + 4)(x - 3) = 3x^2 - 5x - 12
    Does not equal 3x^2 + 5x - 12

  • math - ,

    just switch your signs

    3x^2+5x-12=0
    (3x-4)(x+3) = 0
    so 3x-4 = 0 or x+3 = 0
    x = 4/3 or x = -3

    your version would give a middle term of -5x

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question